Review of organic functional groups : - Lemke, Thomas L (Lippincott Williams & Wilkins, 2003)
This text outlines the functional groups common to organic chemistry, reviewing the general topics of nomenclature, physical and chemical properties, and metabolism. The text provides background material for the formal pharmacy courses in medicinal chemistry, easing the transition from general organic chemistry courses required of all pre-pharmacy students. The Fourth Edition will include a workbook on CD-ROM as well as an index on general drug metabolism